Ethyl Lauroyl Arginate (LAE): Antimicrobial Activity of LAE-Coated Film for the Packaging of Raw Beef and Pork. (19th March 2021) - Tirloni, Erica; Bernardi, Cristian; Stella, Simone
Abstract : In this study, the antimicrobial activity of an ethyl lauroyl arginate- (LAE®-) coated film applied to the packaging of raw beef and pork was evaluated. Two different trials were performed for each meat species, aiming to evaluate the functionality of the film in contrasting the development of the natural microflora and of a specific target agent, Escherichia coli ATCC 25922. In the first trial, LAE-coated packaging was applied to test its activity towards the natural meat microflora over a period of 24 days at 6-7°C. The comparison with the control sample series showed a slight initial inhibitory activity on total viable count, followed by a growing trend. In the second trial, the antimicrobial activity of the LAE-coated film was evaluated on raw beef and pork voluntarily inoculated with Escherichia coli : an initial killing effect on E. coli was detected in both pork and beef meat (reduction around 0.7 and 1 log CFU/g, respectively), followed by a stable trend for the following storage period (24 days).